2020
DOI: 10.1128/jcm.01442-20
|View full text |Cite
|
Sign up to set email alerts
|

Automated Multireplicate Quantification of Persistent HIV-1 Viremia in Individuals on Antiretroviral Therapy

Abstract: Clearance of low-level viremia that persists in most HIV-1 positive individuals on antiretroviral therapy (ART) is an important milestone for efforts to cure HIV-1 infection. The level of persistent viremia on ART is generally below the lower limit of quantification (LOQ) of current FDA-cleared plasma HIV-1 RNA assays (20-40 copies/mL) but can be quantified by RT-PCR assays with single copy sensitivity. Such assays require multistep manual methods and their low throughput limits capacity to monitor the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The single copy RNA assay has shown that most clinically suppressed patients have persistent low-level viremia but it has only been used in research and clinical trial contexts [18,21,[23][24][25][26] and has the disadvantage of a limited range from 0 to 20 copies. The Double-R assay has an improved dynamic range of at least 3 log 10 copies making it more suitable for routine clinical monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The single copy RNA assay has shown that most clinically suppressed patients have persistent low-level viremia but it has only been used in research and clinical trial contexts [18,21,[23][24][25][26] and has the disadvantage of a limited range from 0 to 20 copies. The Double-R assay has an improved dynamic range of at least 3 log 10 copies making it more suitable for routine clinical monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why viral reservoir size and the emergence of pLLV were not correlated by Widera et al (2017) [ 132 ]. Moreover, from the studies reviewed, Jacobs et al were unable to identify a cellular or titular reservoir contributing to persistent viremia and thus proposed proviral replication as the main cause of the continuous presence of the virus [ 133 ].…”
Section: Non-aids Defining Events (Nades) and Pllvmentioning
confidence: 99%
“…These studies used relatively fewer reps (9 to 18 reps) than reported in the current study, but this difference had only a small impact on the rates of detection and estimated viral loads linked to interventions. Furthermore, Jacobs et al evaluated the replicate Aptima assay using 9 reps in comparison to the manual single-copy assay targeting integrase (iSCA v2), showing comparable sensitivity ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%